Public Complaint Management in Traffic Accident Compensation: Evaluating the Organizational Capacity of PT. Jasa Raharja North Sumatra - Anhar, Utari Amilia; Rossevelt, Franklin Asido (Journal of Social and Policy Issues, 2025)
The increasing number of traffic accidents in Indonesia demands effective management of public complaints, particularly in the provision of compensation by PT. Jasa Raharja. This study aims to evaluate the organizational capacity of PT. Jasa Raharja North Sumatra Branch in handling such complaints. Employing a descriptive qualitative approach, data were collected through interviews, field observations, and document analysis involving compensation staff, administrative officials, and accident claimants. Findings indicate that limited human resource capacity—especially in the areas of socialization and public communication—has significantly hindered the effectiveness and timeliness of claim resolution. The shortage of personnel has led to inadequate outreach, long processing times, and a lack of clarity in procedures, which contributes to public confusion and dissatisfaction. Additionally, the absence of proper information infrastructure, such as clear signage and accessible guidelines, further complicates the complaint process. Although the institution fulfills compensation obligations according to regulations, insufficient public understanding regarding the basis of payment calculations has created perceptions of unfairness. This study concludes that strengthening human resources, improving service infrastructure, and developing a more transparent and structured complaint management system are crucial to enhancing public trust and service efficiency. Future research is recommended to include broader regional comparisons and quantitative assessments to support continuous improvement.